Production of nitric oxide and TNF-a, and expression of iNOS and NFkB in peritoneal macrophages activated with interferon gamma (2002)
ABSTRACT : Interferon gamma (IFN-V) is a cytokine produced by cells from the immune system, such as T-cells and natural killer (NK) cells. This molecule has several effects on macrophage (MO) activities including stimulation of the respiratory burst and in vitro enhancement of antimicrobial activity of Mės against bacterial, fungal and mycobacterial organisms. It is known that peritoneal murine Mos, once activated with IFN-Y, exert a fungicidal effect against some pathogenic fungi, including Paracoccidioides brasiliensis, and that this mechanism is mediated by nitric oxide (NO). In addition, it has been demonstrated that IFN-Y is important in the in vivo control of certain mycotic infections. Our purpose was to determine if in vitro, IFN-y-activated peritoneal murine Mos participate in the production of both nitric oxide (NO) and TNF-a, and if the corresponding mechanisms implicated the inducible nitric oxide synthase (iNOS) and nuclear factor (NF-KB) expression. The results showed that the IFN-Y-activated Mos had an increase in both NF KB and iNOS expressions at 6 and 18 h, respectively, indicating a high NO production but a non-detectable TNF-a production. These data suggest that NF-KB expression preceded iNOS expression, inducing both high NO production and IFN-y-activation. Apparently, the latter cytokine by itself is not sufficient to induce TNF-a production on peritoneal murine MOs.